2019
DOI: 10.1016/j.heliyon.2019.e02318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel Schiff bases containing arylpyrimidines as promising antibacterial agents

Abstract: Pursuing our recent interest regarding the antimicrobial activity of Schiff bases derivatives, we have synthesized a series of 6-(substitutedphenyl)- N' -(( E )-(substitutedphenyl)methylidene)-2-methylpyridine-3-carbohydrazides ( 5a-n ) and evaluated their antibacterial activity. Structures of these compounds were confirmed by standard studies of FTIR, 1 H NMR, 13 C NMR, MS and elemental analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In recent years, imine bases demonstrated excellent antibacterial activities with some studies reporting that it possesses better inhibition activity than some commonly used antibiotics [ 39 ]. Although imine bases are continuously being evaluated for their antimicrobial properties against bacteria, there are fewer studies when it comes to P. gingivalis growth inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, imine bases demonstrated excellent antibacterial activities with some studies reporting that it possesses better inhibition activity than some commonly used antibiotics [ 39 ]. Although imine bases are continuously being evaluated for their antimicrobial properties against bacteria, there are fewer studies when it comes to P. gingivalis growth inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the compounds MIC was determined by spotting 5 µL of each concentration of L1 – L5 and Q1 – Q15 on the MHA plates, and the plates were incubated at 37 °C for 18 h. These procedures were done in triplicate to give the accurate lowest concentration of the compounds where no visible bacterial growth was seen after incubation. Ciprofloxacin was used as a standard and DMSO used as a negative control showed no bactericidal effect against all the bacteria strains [ 50 , 62 , 103 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on the synthesis of azomethine compounds have been reported [42,43], but they all suffer from one or more serious shortcomings, such as high environmental pollution due to the solvent and reaction hardness, high temperature, multistep pathways, and long reaction times with low-to-moderate yields under severe reaction conditions. Recently, one of the most intriguing areas in the synthesis of widely used organic compounds is the focus on benign environmentally friendly conditions and reagents such as catalysts.…”
Section: Comparative Synthesis Of Compounds 3(a-c) Comparative Studymentioning
confidence: 99%